(untitled) (Sains Humanika, 2019)
Qibla is the direction in which Muslims have to follow when performing their prayers.Â As claimed by the Islamic Shariâ€™a, when performing prayers, the qibla direction must be accurate towards the Kaaba.Â This claim is not an issue for Muslims living near Mecca but for Muslims living in distant countries from the Mecca, the qibla direction accuracy is a problem that requires immediate settlement decision. Geographically, Malaysia is located 5000 km away from the Mecca, and if the qibla direction deflected for only one degree, it will stray up to 180 km from the Kaaba. The objective of this study is to examine and compare the accuracy of smartphones, theodolites and the istiwaâ€™ sticks during the istiwaâ€™ aâ€™dzam phenomenon because it is the best method of revision to obtain the accurate qibla direction.Â In this study, istiwaâ€™ aâ€™dzam observations have been conducted at Kuala Lumpur Islamic Center Complex on July 16th 2016 at 5:28 pm. The observation results showed that the direction shown by the theodolite is accurate while the use of smart phones showed a difference up to 2Â° from the actual direction of the Kaaba (Baitullah).